PENDAMPINGAN PENULISAN LKS BAGI GURU PONDOK PESANTREN MAZROILLAH KOTA LUBUKLINGGAU - Muhtadin Muhtadin; Satinem Satinem (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2021)
Community service aims to: 1) motivate the Mazroillah Islamic Boarding School teachers to compile their own LKS assisted by QR Codes according to the needs of students and teachers who have their own characteristics; 2) Creating worksheets that suit the needs of teachers and students; 2) Utilizing the potential of teachers to use the QR Code-based worksheets that they created; 3) Produce interesting worksheets; 4) train and familiarize teachers with writing in any form, whether scientific, non-scientific, or writing worksheets; 5) prepare teachers to be able to follow IT developments. The problems faced by teachers at Mazroillah Islamic Boarding School are as follows: 1) lack of reference sources (literature); 2) difficulty in creating LKS with the help of QR Code; 3) Difficulty in determining the right material with the help of a QR Code. The solutions offered in community service activities are carried out by: 1) Providing opportunities for teachers to review the Competency Standards / KI and Basic Competencies (KD) contained in the 2013 KK to be used as the basis for writing LKS; 2) Making teachers independent in using learning resources and not always depending on the school; 3) Provide motivation and enthusiasm that teachers are able to produce quality worksheets so that they can compete with book publishers; 4) Train teachers to have writing skills, both writing scientific works and worksheets; 5) provide opportunities for collaboration between STKIP-PGRI Lubuklinggau institutions and partner schools in terms of library utilization